Analysis of Mathematical Communication Ability in Solving Story Problems Based on Mathematical Ability and Gender - Yunita, Mardhiyah; Siswanto, Rizki Dwi (Universitas Wiralodra, 2023)
This study aims to test the written mathematical communication skills of students who st udy mathematics material about cubes and blocks at SMP 238 Jakarta. This study uses a qualitative descriptive methodology. Data collection using tests and interview. As a test of the v alidity of the data usin the triangulation technique was carried out by comparing the results of the subject’s mathematical communication ability test with the results of the interview. The subject of this study were students of class VIII SMP 238 Jakarta, totaling 6 students who were divide into 3 groups based on high, medium, and low level of mathematicl ability. This study uses 3 indicators, namely explaining mathematical ideas, situations and relationships/in writing, explaining mathematical ideas in the form of visual images/tables/diagrams, explaining ideas of problem situations picture or real objects into the language of symbols of mathematical models/mathematical expressions. This study revealed that students with high level of mathematical ability were able to answer questions on indicators 1, 2, and 3. Subjects with low level of mathematical ability were able to answer questions on indicators 1, 2, and 3 but still did not understand and were still in complete the method used in answering.